Administration of medication to use when needed and the care of psychiatric nursing - Kelly da Silva Rocha Estrela; Cristina Maria Douat Loyola (Associação Brasileira de Enfermagem, 2014)
This qualitative study aimed to analyze the clinical criteria used for the administration of prescribed medications for use when needed (SOS); and discuss the implication of the findings in this research to clinical psychiatric nursing. The records of female patients admitted to a psychiatric institution in the city of Rio de Janeiro, in the time frame from May to June 2009, were analyzed. In the 38 patient records, 16 prescriptions for medications SOS were found. The mean age of patients was around 45-55 years with a clinical diagnosis of Bipolar Mood Disorder. The medication category most prescribed as SOS was of benzodiazepines, followed by antipsychotics. It was noticed a tendency to not valuing the administration of medication in SOS notes. The study points out the importance to establish clinical criteria to indicate the need, or not, to administer prescribed SOS medications.